2014
DOI: 10.5535/arm.2014.38.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Pressure Distribution During Robotic-Assisted Gait in Post-stroke Hemiplegic Patients

Abstract: ObjectiveTo assess the plantar pressure distribution during the robotic-assisted walking, guided through normal symmetrical hip and knee physiological kinematic trajectories, with unassisted walking in post-stroke hemiplegic patients.MethodsFifteen hemiplegic stroke patients, who were able to walk a minimum of ten meters independently but with asymmetric gait patterns, were enrolled in this study. All the patients performed both the robotic-assisted walking (Lokomat) and the unassisted walking on the treadmill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Secondly, we must take into account the small sample size of our healthy volunteers and their young age (mean: 25 ± 4 years), which also had no gait pathologies. Thus, RA guidance of gait movement might have different effects in elderly subjects or patients who are not able to walk without restrictions [96]. Therefore, the findings from our study are difficult to apply to other age or patient groups, as neurological patients often suffer from movement disorders and therefore use different control strategies during RAW.…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, we must take into account the small sample size of our healthy volunteers and their young age (mean: 25 ± 4 years), which also had no gait pathologies. Thus, RA guidance of gait movement might have different effects in elderly subjects or patients who are not able to walk without restrictions [96]. Therefore, the findings from our study are difficult to apply to other age or patient groups, as neurological patients often suffer from movement disorders and therefore use different control strategies during RAW.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, ankle immobilization by ankle straps has been reported to limit gait improvement [7]. Therefore, RAG training does not increase walking speed more than overground gait training and other forms of physiotherapy, but their effects on walking distance are not clear [17].…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the effects of the RAG on gait improvement, differences in foot pressure distribution during walking between RAG training and BWSTT were studied [16]. It was also found that BWSTT and RAG training do not increase walking speed more than overground gait training and other forms of physiotherapy, but their effects on walking distance are not clear [17]. Therefore, almost no research has been conducted to determine the differences in gait between the RAG condition, which moves by active assist under the help of a robot, and the active independent over-ground gait (IOGG) condition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we think the experimental group’s gait improved in comparison to the control group because the training used an ankle strategy to distribute weight evenly between the left and right side and to displace the COP laterally, and antero/posteriorly increased the COP displacement lengths that had been shortened. Yang et al 18 ) reported that patients with hemiplegia due to stroke showed improvement in their gait index after gait training using robots. In that study, the patients’ COP displacement increased a finding that is similar to the results obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%